Diseño y construcción de un elevador vertical manual tipo apilador para una carga máxima de 300 kg. - Gavilanes Carrasco, Francisco Javier (2014)
This project includes the calculus, the design and the construction of a vertical elevator type manual stacker for a maximum load of 300 kg and a maximum lifting height of 5000 mm measured from the bottom of the elevator. The purpose is to meet the specific need of JYXCEM CIA. LTDA Company which lends its service to public and privates institutions as contractors providing installations and maintenance of aerial telecommunications networks industrial. The chapter one deals with general information about different types of existent elevators and none existent in the national market as well as its use in the industry, features, parts and labor.